دراسة تأثير نظام الإنتاج العضوي في مواصفات ثمار صنف الزيتون الدعيبلي ونسبة الزيت ومؤشرات جودته - مخول جرجس; نداف محمد; أحمد محمد; قطمة غادة; مخول سهيل; حمود نزار; مصة وسام; داوود محمود (Latakia University Journal -Biological Sciences Series, 2018)
This research was conducted during the seasons 2015- 2016, in collaboration between Ministry of High Education and General Commission of Agricultural Scientific Research (GCSAR). It was funded equally by the two participating parties. In order to study the the impact of the organic production system on an orchard planted with the olive variety Doebli in the region of Safita. The orchard was divided in to two plots with area of 1 dunum (1000 m2), one of them was managed under organic system according to Syrian organic law, while conventional practices used by farmer were applied in the second plot. These plots were separated by two row of olive trees. The characteristics of fruits (weight of fruits and pulp/ fruit percentage) were studied in the laboratory of the Department of Food Science at the Faculty of Agriculture, Tishreen University,and also The fruit content of wet oil and its composition of the essential fatty acids were determined. The oil content of total phenols and its absorption at 232 and 270 nm were observed, in addition to the free acidity% and peroxide value of oil produced by organic and conventional treatment. The results showed that the yield of olive oil was significantly higher in the experimental organic plot in terms of weight and the pulp/ fruit percentage (4.1g, 73.55%) compared with the conventional plot (2.88 g, 68.6%),the fruits content of wet oil and the ratio of essential fatty acid oleic increased in organic treatment by (2.9% and 1.53%, respectively). The results of the chemical analysis also showed the superiority of the oil produced organically in term of its polyphenols content (increase of 92.45 mg / kg oil) and other quality indicators. The absorption values at 232 nm, free acidity, and peroxide value were lower in the oil produced from organic plot, which gives it a stability during storage against oxidation factors. The application of the organic olive production system contributes to increasing the production of fruits and oil, and ensures the acquisition of high quality olive oil, which opens the way for export it to foreign markets and gain a greater margin of profit for the farmer and contribute to support the national income. أجري هذا البحث خلال الموسمين 2015 – 2016 كجزء من مشروع مدرج باتفاقية التعاون بين وزارة التعليم العالي والهيئة العامة للبحوث العلمية الزراعية وتم تمويله مناصفة من الجهتين المشاركتين، وذلك بهدف دراسة تأثير تطبيق نظام الإنتاج العضوي على بستان مزروع بصنف الزيتون الدعيبلي في منطقة صافيتا، حيث تم تقسيم بستان الزيتون لقطعتين مساحة كل منهما واحد دونم، و طبق على أحدها معاملات الإنتاج وفق القانون السوري للإنتاج العضوي، بينما طُبقت المعاملات التقليدية المتّبعة من قبل الفلاح على القطعة التجريبية الأخرى (الشاهد). دُرست مواصفات الثمار (وزن الثمار ونسبة التصافي) وقد تم تحديد محتوى الثمار من الزيت الرطب وتركيبه من الأحماض الدهنية ، كما تمت دراسة المحتوى من البولي فينولات الكلية والامتصاصية عند طولي موجة 232 و270 نانو متر والحموضة الحرة% ورقم البيروكسيد للزيت الناتج عن المعاملتين العضوية والتقليدية في مخابر قسم علوم الأغذية في كلية الزراعة بجامعة تشرين. أظهرت النتائج تفوّق ثمار الزيتون الدعيبلي في القطعة التجريبية العضوية معنويّاً من حيث وزنها ونسبة التصافي (4.1 غ، 73.55%) مقارنة بمثيلاتها في القطعة التقليدية (2.88 غ، 68.6%)، كما ارتفع محتوى الثمار من الزيت ونسبة الحمض الدهني الأساسي الأولييك في المعاملة العضوية بمقدار (2.9%، 1.53% على التوالي). بينت نتائج التحاليل الكيميائية أيضاً تفوق الزيت المنتج عضوياً من حيث محتواه من البولي فينولات (مقدار الزيادة 92.45 ملغ/ كغ زيت) وبمؤشرات جودته الأخرى، بالمقارنة مع الزيت المنتج بالطريقة التقليدية؛ إذ كانت قيم الامتصاصية عند طول موجة 232 نانومتر والحموضة الحرة%، والبيروكسيد أقل في الزيت المنتج من القطعة العضوية مما يكسبه صفة الثباتية أثناء التخزين ضد عوامل الأكسدة. إن تطبيق نظام الإنتاج العضوي للزيتون يسهم في زيادة الإنتاج من الثمار والزيت فيها، ويضمن الحصول على زيت زيتون عالي الجودة، مما يفتح المجال واسعاً أمام تصديره للأسواق الخارجية وزيادة الطلب عليه، والحصول على هامش ربح أكبر للمزارع ويسهم في دعم الدخل الوطني.